BANDWIDTH MANAGER MENGGUNAKAN HIERARCHICAL TOKEN BUCKET PADA IMPLEMENTASI VIDEO STREAMING - Soba, Saryadi K T; Rachamawati, Rr.Yuliana; Raharjo, Suwanto (Jurnal Jarkom, 2015)
ABSTRACTScience and technology are increasingly evolving, has brought a wide range of new breakthrough, one that is increasingly technologically sophisticated and modern. This also participate in the field of computerization, computers that previously had limited functions only as a mere data processing, but now is able to play a major role in peoples lives everyday.Streaming video service is now urgently needed. It is characterized by many organizations or institutions that use streaming video access in bulk. The use of video streaming en masse this Â network performasi downs along with the increasing number of users. One way to reduce the decline in performance is to set the bandwidth.Hierarchical Token Bucket (HTB) as implementer management of bandwidth available for free and can be run on Linux Operating system platform is a viable Bandwidth Manager analyzed their advantages and disadvantages, is expected to use proper and accurate will create a network that implements Bandwidth Manager is working optimallyKeywords: HTB, limit, bandwidth.